Pengaruh Social Media Marketing Dan Electronic Word Of Mouth (E-Wom) Terhadap Purchase Intention Dengan Trust Sebagai Variabel Mediasi Pada Konsumen Tara Coffe Shop Di Kota Padang - Muhammad Fachri Putra Restu Adi fachri; Alvin Alfian (CV. Akira Java Bulu, 2026)
This study aims to examine the influence of social media marketing and electronic word of mouth (e-WOM) on purchase intention of Tara Coffee Shop Padang products, with trust as a mediating variable. Using a quantitative approach, data were collected through questionnaires distributed to 180 respondents who had experience purchasing Tara Coffee Shop products. Analysis was conducted using Partial Least Squares (PLS) to assess the direct and indirect relationships between variables. The results showed that social media marketing has a positive and significant influence on purchase intention. Electronic word of mouth has a negative and significant influence on purchase intention. Social media marketing has a positive and significant influence on trust. Electronic word of mouth has a positive and significant influence on trust. Social media marketing has a positive and significant influence on purchase intention, which is mediated by trust. Electronic word of mouth has a positive and significant influence on purchase intention, which is mediated by trust.